(untitled) (Journal of Academic Research, 2023)
The endpoint of fixed prosthesis design is an esthetic and functional pontic that is compatible with soft-tissue health. The current study aimed to assess the knowledge and practice of Pontic design selection by the general dental practitioners (GDPs). This cross-sectional study was conduct among the GDPs of Misrata. A questionnaire was design to collect data from 110 GDPs. The questionnaire included general/demographic information and an average number of fixed prosthesis constructed by the GDPs. The questionnaire was further categorize to evaluate the knowledge/practice of Pontic design selection and latest recommendations. For the maxillary anterior segment, the ridge lap Pontic was the most common (43%) followed by the conical (28%). In the maxillary posterior segment, the ridge lap Pontic was the most common (56%) followed by ovate design (23%). For the mandibular anterior segment, the ridge lap (44%) was the most common followed by modified ridge lap Pontic (27%). In case of the mandibular posterior segment, the ridge lap design (64%) was the most common followed by conical Pontic (18%). In the posterior segment, where esthetics is not as critical, a sanitary pontic form is most compatible with function and hygiene. In anterior region, esthetics is an important concern along with function and space management. ​In the maxillary anterior region, a properly contoured modified ridge-lap pontic design constructed of glazed porcelain most readily fulfills both the esthetic and physiologic requirements. The Pontic design selection for the fixed prosthesis is a neglected domain.